Review of Uncertainty Modeling for Optimal Operation of Integrated Energy System - Fan, Hong; Wang, Cuiying; Liu, Lu; Li, Xuan (Frontiers in Energy Research, 2022)
The operation of the integrated energy system is affected by uncertainties, leading to sub-optimal decisions. Accurate and effective modeling of these uncertainties is essential to ensure the optimal integration of renewable energy in the integrated energy system. This article first analyzes the characteristics of various uncertain factors in the optimal operation of the integrated energy system.The source side mainly considers the intermittent and volatility of renewable energy output, The load side mainly considers the load forecast error and the uncertainty of the demand side response. The network side mainly considers the uncertainty of equipment performance due to factors such as poor debugging, aging, ineffective maintenance, the uncertainty of the coupling of the multi-energy flow system, and the uncertainty of the cyber-physical system.The multi-energy trading market mainly considers the uncertainty of market rules and energy prices. Then,the various modeling methods are summarized. Finally, it looks forward to the future research directions and challenges faced by the optimization of the integrated energy system considering the uncertainty.